Phase I Pharmacokinetics Study of Drug Areplivir® Zinc (INN: Favipiravir + Zinc Gluconate) (LLC "PROMOMED RUS", Russia) - T. N. Komarov; N. S. Bagaeva; K. K. Karnakova; O. A. Archakova; D. S. Shchelgacheva; V. S. Shcherbakova; K. Ya. Zaslavskaya; P. A. Bely; A. V. Taganov; I. E. Shohin (Разработка и регистрация лекарственных средств)
Introduction. Favipiravir is an antiviral compound that inhibits the RNA-dependent polymerase and possesses antiviral properties against RNA viruses, including SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2). The new drug Areplivir® Zinc as a combination of favipiravir (200 mg) and zinc gluconate (70 mg) in the form of film-coated tablets has been developed by LLC "PROMOMED RUS", Russia. This combination of favipiravir and zinc gluconate could provide more effective treatment of COVID-19.Aim. The aim of the pharmacokinetics study is comparison between Areplivir® Zinc (INN: favipiravir + zinc gluconate), film-coated tablets (the manufacturer is JSC "Biokhimic", LLC "PROMOMED RUS" as registration certificate holder) and Areplivir® (INN: favipiravir), film-coated tablets (the manufacturer is JSC "Biokhimic", LLC "PROMOMED RUS" as registration certificate holder) to evaluate the effect of zinc on the favipiravir pharmacokinetics.Materials and methods. The clinical and analytical phases as well as pharmacokinetic analyses have been performed as a part of a phase I clinical trial. Chromatographic separation and detection of favipiravir were performed by high-performance liquid chromatography – tandem mass spectrometry (HPLC-MS/MS) method using Nexera XR high-performance liquid chromatograph with triple quadrupole tandem mass spectrometer LCMS-8040 (Shimadzu Corporation, Japan). The validated analytical range of the method was 50.00–15 000.00 ng/mL in human plasma. The plasma zinc concentrations were measured by a biochemical method with the use of the kit «Zinc-Novo (50)» (JSC "Vector-Best", Russia). The descriptive statistics were calculated using Microsoft Excel (Microsoft Corporation, USA). The pharmacokinetic parameters, analysis of variance (ANOVA), 90 % confidence intervals (90 % CIs) and the intra-subject variability (CVintra) were calculated by R Project 3.5.1 software (package «bear», version 2.8.3-2), originally created by Hsin-ya Lee and Yung-jin Lee, Taiwan.Results and discussion. The 90 % confidence intervals of the ratios for Сmax and AUC(0–t) were 86.48–100.38 % and 103.77–119.47 %, respectively. The 90 % confidence intervals were all within the acceptance range of 80.00–125.00 % which means there is no effect of zinc on the favipiravir pharmacokinetics. The intra-subject variability (CVintra) of favipiravir for the pharmacokinetic parameters Cmax and AUC(0–t) were 15.06 % and 14.23 %.Conclusion. The results justified the subsequent phases of clinical trials of Areplivir® Zinc (INN: favipiravir + zinc gluconate), film-coated tablets (LLC "PROMOMED RUS", Russia). This combination of favipiravir and zinc could expand the existing armamentarium of antiviral drugs for the treatment of COVID-19.